2021
DOI: 10.3389/fvets.2021.736739
|View full text |Cite
|
Sign up to set email alerts
|

Biological Function of Short-Chain Fatty Acids and Its Regulation on Intestinal Health of Poultry

Abstract: Short-chain fatty acids (SCFAs) are metabolites generated by bacterial fermentation of dietary fiber (DF) in the hindgut. SCFAs are mainly composed of acetate, propionate and butyrate. Many studies have shown that SCFAs play a significant role in the regulation of intestinal health in poultry. SCFAs are primarily absorbed from the intestine and used by enterocytes as a key substrate for energy production. SCFAs can also inhibit the invasion and colonization of pathogens by lowering the intestinal pH. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 143 publications
(155 reference statements)
3
67
0
2
Order By: Relevance
“…This was in line with in several studies indicating the effects of SCFA on intestinal immunity as reviewed by Gasaly et al (2021) . It was proposed that SCFA may regulate cytokine production of the immune or epithelial cells by directly binding to certain receptors such as free fatty acid receptor (or G protein-coupled receptors) and/or by regulating target cell epigenetics after they were taken up into the cells ( Liu et al, 2021 ). Among SCFA, propionate demonstrated a relatively strong positive correlation with most of cytokines analyzed in this study, especially IL-4, IFN-γ and TGF-β2.…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with in several studies indicating the effects of SCFA on intestinal immunity as reviewed by Gasaly et al (2021) . It was proposed that SCFA may regulate cytokine production of the immune or epithelial cells by directly binding to certain receptors such as free fatty acid receptor (or G protein-coupled receptors) and/or by regulating target cell epigenetics after they were taken up into the cells ( Liu et al, 2021 ). Among SCFA, propionate demonstrated a relatively strong positive correlation with most of cytokines analyzed in this study, especially IL-4, IFN-γ and TGF-β2.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that SCFAs are closely associated with inflammation. They protect the integrity of the intestinal epithelium and promote the intestinal immune response, thereby protecting the intestinal wall and reducing the incidence of intestinal inflammation ( Liu et al, 2021 ). It has been demonstrated that SCFAs can effectively inhibit the inflammatory response of Caco-2 cells and maintain the tight junctions of intestinal mucosal epithelial cells ( Xi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sections were observed under an upright microscope (Eclipse E200, Nikon, Japan) and photographed using ImageView (Pooher, Shanghai, China). The histologic scores were evaluated as described previously (Guo et al, 2021), a score of 0-4 was given depending on the number of lesions in the colon and their severity.…”
Section: Histological Analysismentioning
confidence: 99%
“…Важная функция Firmicutes -это способность разлагать сложные полисахариды с последующим образованием короткоцепочечных жирных кислот (30). Короткоцепочечные жирные кислоты играют важную роль в энергетическом метаболизме хозяина, способствуя росту и нормальному функционированию клеток кишечника (31).…”
unclassified
“…По мнению L. Liu с соавт. (31), протеолитические системы и селективный протеолиз рассматриваются в качестве ключевых регуляторов процессов опухолевой прогрессии; процессы протеолиза имеют непосредственное отношение к реакциям воспаления и деструкции тканей.…”
unclassified